Diagnostics of the Deformation Properties of Grained Materials - Libor Izvolt; Milan Milan Miksik (Communications - Scientific letters of the University of Zilina, 2001)
In the field of substructure of line and ground building works, natural grained materials have considerable representation in the material basis. During the exclusive offer of these materials suppliers, it is necessary to determine the possibilities of material use into traffic-way structure. The suitability of using natural-grained materials can be judged in laboratory conditions. In the paper a method is characterised to be applicable for the complex judgement of variousmaterial use in construction layers of the traffic way or for diagnostics of the building works before their opening. Material suppliers can document the quality of the supplied material as a basic presumption of the whole traffic works, which can be judged not only with this method application but also in its marked offer documentation.